PENGARUH MOTIVASI, KOMITMEN KARYAWAN DAN KEPUASAN KERJA KARYAWAN TERHADAP LOYALITAS KERJA KARYAWAN BAGIAN LOKET DI PT.TRANSPORTASI JAKARTA - Yanti, Apry Ficry; Saragih, Lisnatiawati (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2022)
This study aims to analyze the influence of motivation, employee commitment, and job satisfaction of employees at the stage of job loyalty of employees at the counter at PT. Jakarta Transportation. The population is 70 employees of the counter in corridor 5. The data retrieval method uses a saturated sampling technique and the analysis method used a component or variance based structural equation model where the data processing uses the Partial Least Square (Smart-PLS) version 3.0 PLS program. The results of this study indicate that motivation employee commitment and employee job satisfaction have a positive and significant effect on job loyalty.